2005
DOI: 10.1016/s1015-9584(09)60272-4
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Antibiotic Administration in Elective Surgical Procedures: Still Missing the Message

Abstract: Objective: The aim of this study was to determine the appropriateness of antibiotic prophylaxis in selected elective surgical procedures in a tertiary referral centre. Methods: A cross-sectional study using retrospective data from January 2000 to May 2002 was performed pertaining to elective colorectal surgery, cholecystectomy and inguinal hernia repairs. Appropriateness of antibiotic administration was determined based on compliance with national and internationally accepted guidelines on prophylactic antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 12 publications
2
22
0
Order By: Relevance
“…Similar studies conducted in other countries (8)(9)(10)(11)(12)(13)(14)(15)(16), revealed a high frequency of prescription of antibiotics when not required, inappropriate choice, and use of antibiotics for a prolonged duration. In the current study too, a similar prescription pattern was found, where 3rd generation cephalosporins were prescribed to all patients preoperatively.…”
Section: Discussionsupporting
confidence: 71%
“…Similar studies conducted in other countries (8)(9)(10)(11)(12)(13)(14)(15)(16), revealed a high frequency of prescription of antibiotics when not required, inappropriate choice, and use of antibiotics for a prolonged duration. In the current study too, a similar prescription pattern was found, where 3rd generation cephalosporins were prescribed to all patients preoperatively.…”
Section: Discussionsupporting
confidence: 71%
“…However, other articles showed results inferior to the aforementioned frequencies, with a variation for the use of the antibiotic prophylaxis in the range of 58% to 73% [17][18][19] .…”
Section: Resultsmentioning
confidence: 99%
“…Intermediate values have been reported for this outcome, between 61.1% and 84% 18,20,21,23,28 . However, Gul et al 19 and Tourmousoglouv et al 16 observed rates of 98% and 100%, respectively, representing appropriate values. The timing of administration of prophylactic antibiotics should obey the time it takes to reach the blood and tissue concentrations that exceed the minimum inhibitory concentration for the microorganisms likely to colonize the surgical site 31,32 .…”
mentioning
confidence: 95%
“…Several studies assessing compliance with surgical prophylaxis guidelines in hospitals abroad have been published [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Overall compliance to guidelines has varied from as low as 0-53%, usually in the range of 20-30%.…”
Section: Discussionmentioning
confidence: 99%